2010
DOI: 10.1016/j.juro.2009.08.147
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Testicular Pain as a Symptom of Pelvic Floor Dysfunction

Abstract: Chronic testicular pain can be a symptom of pelvic floor overactivity, especially in younger patients. A diagnostic evaluation should be performed when no pathophysiology can be found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Scrotal pain could be due to either referred pain or idiopathic pain, and the testicular causes of pain include infection, tumor, testicular torsion, varicocele, hydrocele, spermatocele, trauma, or previous surgical intervention (12). Organs and body structures that share nerve pathways with scrotal structures, such as the ureter, the prostate or the hip, can cause referred pain in this area (12,13). Scrotal US is an important component of the evaluation of patients with scrotal pain (14).…”
Section: Discussionmentioning
confidence: 99%
“…Scrotal pain could be due to either referred pain or idiopathic pain, and the testicular causes of pain include infection, tumor, testicular torsion, varicocele, hydrocele, spermatocele, trauma, or previous surgical intervention (12). Organs and body structures that share nerve pathways with scrotal structures, such as the ureter, the prostate or the hip, can cause referred pain in this area (12,13). Scrotal US is an important component of the evaluation of patients with scrotal pain (14).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found 93% of the 41 men had at least 1 symptom of pelvic floor dysfunction. In subsequent pelvic floor testing using electromyography registration, 88% of patients had increased resting pelvic floor muscle tone with mean of 6.7 mV (normal <3.0 mV) (21). Men with a normal resting pelvic floor tone were significantly older than those with an increased resting tone (65.6 vs. 45.6 years, P=0.0001) which supported the possibility of pelvic floor dysfunction in younger men with chronic orchialgia (21).…”
Section: Diagnosis and Evaluationmentioning
confidence: 99%
“…Most papers in the literature cite causes for chronic orchialgia such as post-vasectomy pain syndrome, inflammatory chronic epididymitis, trauma, tumor, torsion, diabetic neuropathy, vascular anomalies, postoperative scrotal pain, chronic prostatitis, and rarer causes such as schistosomiasis and tuberculous epididymitis (1,2,22). Psychosomatic components of chronic orchialgia are poorly understood and infrequently considered as a cause of physical pain.…”
Section: Psychosomatic Componentsmentioning
confidence: 99%